PEMBERDAYAAN MASYARAKAT DESA MALAWOR DISTRIK MAKBON KABUPATEN SORONG (STUDI TENTANG PROGRAM PERCETAKAN SAWAH) - TAHRIN, NOVALIA; RARES, JOYCE; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
Empowerment according to the Big Indonesian Language Dictionary (KBBI) is a process, method, actionthat makes power, namely the ability to do something or the ability to act in the form of reason, effort oreffort. Society is the unity of human life that interacts according to a certain system of customs that iscontinuous, and which is bound by a sense of shared identity. Community empowerment is an effort toimprove the ability and potential of the community so that the community can realize its identity and dignityto the maximum to survive and develop themselves independently both in the economic, social, religious andcultural fields. Rice field printing programs are carried out to increase food production to support therealization of food security in Indonesia. The purpose of the new paddy field printing activity is to increasethe standard area of pagan land through the expansion of paddy fields which are then expected to be ableto produce the main production of rice in the paddy fields. In addition, the implementation of this programis expected to be able to meet the needs of paddy fields which are decreasing due to land conversion. Therice field printing program is intended to support food self-sufficiency and food security in Indonesia.Keywords: Empowerment, Community and Print Rice Fields